Physiological and quantitative phosphoproteome analyses of drought stress-induced mechanisms in Malus baccata (L.) Borkh. (June 2017) - Ren, Jing; Li, Xinwe; Mao, Juan; Zuo, Cunwu; Zhao, Xin; Chen, Baihong
Abstract: Limited information is available on how fruit crops respond to moderate drought stress. In the present study, we investigated how Malus baccata (L.) Borkh. a drought-tolerant genotype apple rootstock, responds to moderate drought stress. Our results for enzyme activity under moderate drought stress indicated that M. baccata produces osmosis-regulating substances. The phosphoproteins in the leaves were analyzed using iTRAQ technology. In total, 269 unique phosphopeptides, 304 phosphorylated sites, and 219 phosphoproteins were quantitatively analyzed in M. baccata . Furthermore, we identified 46 phosphoproteins in M. baccata whose phosphorylation levels significantly changed (PLSC). Among them, 22 PLSC phosphoproteins were found to be involved in metabolic processes that included carbon and nitrogen metabolism. This suggests that a systematic response pattern was generated in M. baccata and moderate drought stress resulted in a new homeostasis of carbon and nitrogen metabolism. The 14 differentially expressed mRNAs encoding phosphoproteins were analyzed by quantitative real-time PCR. Our study is the first to analyze the phosphoproteome of M. baccata and provides insights into the partial molecular regulatory mechanisms of M. baccata under moderate drought stress. Highlights: We studied the phosphoproteome of an apple genotype under moderate drought stress. 46 phosphoproteins in Malus baccata (L.) Borkh. were significantly regulated under drought conditions. 22 PLSC phosphoproteins were found, by gene ontology analyses, to be involved in carbon and nitrogen metabolism. Some important drought tolerant candidates were identified. Potential schematic representation of a metabolism response model in M. baccata under moderate drought stress.